Prediction Of User Behavior Intention Towards Robo-Advisor Applications In Fintech Using The Utaut Model - Cheong, Suk Fun (2023)
In response to the COVID-19 pandemic, the advancement of automated services in the financial technology (fintech) sector had undeniably sped up tremendously. At the same time, the instability of the financial market and inflation had influenced specific groups of potential and existing investors to reconsider investment choices and re-manage their financial planning. Even though, there is increase of investors across the market however the number of investor using robo-advisory service as their investment option is still considered low. The goal of the study was to examine the significant factors to influence customer’s behavioral intention from the perspective of using financial investment Robo-advisor (RA) in post-COVID-19 pandemic.